Castellar de Meca Revisited: The Islamic Occupation (9th–12th Centuries) - Simón García, José Luis; Moreno-Narganes, José María; Jiménez-Castillo, Pedro (Madrider Mitteilungen, 2024)
Castellar de Meca (Ayora, Valencia) has long been recognized as an outstanding protohistoric archaeological site owing to its enormous size, impressive remnants of cyclopean walls, and, above all, its rock-hewn features which include paths, silos, and cisterns. As a result, the significance of its occupation during the Middle Ages has been overshadowed, despite its substantial material remains. This work aims to analyse the history of Meca during the Islamic period, drawing on surveys, a reexamination of the evidence from excavations conducted by Iron Age specialists, and even historical maps. With this, we seek to demonstrate that the analysis of this site is crucial for two reasons: first, it allows for a better understanding of settlement patterns in the region from the Emirate (9th century) to the Almoravid period (first half of the 12th century). Second, this was the most important settlement in western Valencia during the 11th century. Previously, the region had barely played a marginal agricultural role, but in the 11th century it underwent an intense process of colonisation in the wake of the economic revolution that was taking place in al-Andalus and in other European and Mediterranean regions.